Distance learning in teacher education: emergency, quality benchmarks, public policies, and the pedagogical practice - Felipe Bezerra de Medeiros Dantas Duarte; Marlécio Maknamara (Universidade Estadual de Maringá, 2016)
This paper was inspired by the growth and appreciation that Distance Education (DE) has taken in recent decades in the training of teachers in Brazil. Our main goal is to point transformations regarding distance Education in Brazil, especially in teacher education. Through that, we brought what is being debated these last years about Distance Education. From the results we can say that current transformations in the Brazilian educational scenario, particularly in teacher training and distance education show us that they need to be better understood. Reflecting about many issues DE has, we may conclude that clearly we need more research to answer many of our continuing questions, especially regarding formative needs and teacher learning in the Distance Education context.